2019
DOI: 10.1007/s10531-019-01892-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, fire-induced changes in habitat structure and microclimate affect Cerrado lizard communities

Abstract: Fire transforms the structure of natural habitats and, consequently, modifies microclimates affecting ectotherm organisms that are particularly susceptible to changes in the thermal environment. Nevertheless, the effects of fire-induced microclimatic shifts upon natural populations have been neglected. We measured the central tendency and variation of habitat structural and microclimatic variables in experimental plots of Neotropical savanna vegetation subjected to different fire regimes (control, biennial/ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…So, the homogenization of vegetation structure, as seen in the case of increased woody encroachment in the absence of fire, affecting grassland/savanna specialists (Vieira and Marinho-Filho, 1998;Vieira, 1999;Henriques et al, 2000Henriques et al, , 2006Briani et al, 2004;Maravalhas and Vasconcelos, 2014;Abreu et al, 2017), will disrupt community structure resulting in biodiversity losses. Studies of open formations around the world also highlight the importance of habitat heterogeneity for maintaining biodiversity of the landscape (Andersen et al, 2012;Beale et al, 2018;McCleery et al, 2018;Bond, 2019;Costa et al, 2019). At our study area, open grasslands and savannas have particular importance for conservation at local and regional scales.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…So, the homogenization of vegetation structure, as seen in the case of increased woody encroachment in the absence of fire, affecting grassland/savanna specialists (Vieira and Marinho-Filho, 1998;Vieira, 1999;Henriques et al, 2000Henriques et al, , 2006Briani et al, 2004;Maravalhas and Vasconcelos, 2014;Abreu et al, 2017), will disrupt community structure resulting in biodiversity losses. Studies of open formations around the world also highlight the importance of habitat heterogeneity for maintaining biodiversity of the landscape (Andersen et al, 2012;Beale et al, 2018;McCleery et al, 2018;Bond, 2019;Costa et al, 2019). At our study area, open grasslands and savannas have particular importance for conservation at local and regional scales.…”
Section: Discussionmentioning
confidence: 84%
“…Despite the pattern of low impact on richness observed in most studies, however, there are some exceptions when fire effects are analyzed at a small scale, comparing different pieces of the vegetation mosaic. Costa et al (2019) found half the lizard species favored in unburned plots while the other half was favored in burned plots. These results indicate that maintaining the vegetation mosaic can enhance beta and gamma diversity, a recommendation supported also by Andersen et al (2012), who found advantage for small mammals in preserving some large infrequently burned areas.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…First, the primary effects of fire are indirect through habitat change, which is caused by both individual fires and by different fire regimes. This has been shown for many biomes for a wide range of animal taxa, including ants (Andersen, 2019), reptiles (Costa et al, 2020;Dixon et al, 2018), birds (Gosper et al, 2019;Woinarski & Recher, 1997) and small mammals (Griffiths & Brook, 2014). In particular, fire has a pervasive effect on fauna through its impact on habitat openness (Andersen, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Human-induced environmental impacts also translate into increased frequency and severity of fires in the Cerrado. Costa et al (2020) assessed the effects of fire-induced microclimatic shifts upon Cerrado lizard communities. They found that fire suppression enhanced habitat structural complexity, whereas burning had the opposite effects; half of the lizard species were favoured in the fire-protected plot, while the other half was favoured in burned plots.…”
Section: Synopsismentioning
confidence: 99%